The second Sura as the Centre of the Koran in its relation to Judaism and Christianity - Schmitz, Bertram (Vox Scripturae - Revista Teológica Internacional, 2015)
Historically, is the revelation of the Koran from its beginning in the tension between Judaism and Christianity. Muhammad and his first listeners were well known to both religions, even if these listeners did not belong either to Judaism or Christianity. The submitted statements show how the second Sura, countered  by the emerging Islam in relation to the context of Judaism and Christianity, their positions in detail confirmed, modifies, or rejects. The second Sura can be understood as a through-composed work of art. In similar structure to the Torah it shows how Islam is justified and what he wants. She shows with historical and - in the broad sense of the word - theological arguments, how the other two religions would have to be replaced because they do not (more) embody the true religion of Abraham and thus of God, but have deviated from it and also contradict each other about it.
Keywords: Interfaith Koran interpretation; Judaism and the Koran; Christianity and the Koran